Encyclopedia of Polymer Science and Technology 2017
DOI: 10.1002/0471440264.pst165.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Polymers (Geopolymers)

Abstract: Geopolymers are ceramic-like inorganic polymers produced at low temperature, generally below 100 °C. They consist of chains or networks of mineral molecules linked with covalent bonds. The raw materials are mainly minerals of geological origin, hence the name "geopolymer". They comprise several molecular units for example: silico-oxide (Na,K)-(-Si-O-Si-O-) for (Na,K)-poly(silicate) or (Na,K)-poly(siloxonate), silico-aluminate (Na,K)-(-Si-O-Al-O) for (Na,K)poly(sialate), ferro-silico-aluminate (Na,K)-(-Fe-O-Si-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…The strengths of all the samples was adequate for biomedical applications, but that of the Ca3(PO4)2 sample was slightly greater, making it the more promising material [36]. This brief summary covers only a small part of the work of the New Zealand geopolymer group over the last 20 years, but more extensive details of our work in several of these research areas can be found in the book chapters [37][38][39][40][41][42][43] and summarised in Figure 2.…”
Section: A Brief Summarymentioning
confidence: 99%
“…The strengths of all the samples was adequate for biomedical applications, but that of the Ca3(PO4)2 sample was slightly greater, making it the more promising material [36]. This brief summary covers only a small part of the work of the New Zealand geopolymer group over the last 20 years, but more extensive details of our work in several of these research areas can be found in the book chapters [37][38][39][40][41][42][43] and summarised in Figure 2.…”
Section: A Brief Summarymentioning
confidence: 99%
“…Catalysts 2020, 10, x FOR PEER REVIEW 21 of 21 minerals are commercially valuable, and the use of industrial wastes such as fly ash from coal-fired boilers for specialised geopolymer applications is attracting increasing attention. Several synthetic methods for aluminosilicate geopolymers have been reported [8], but the most widely used is the reaction of a finely divided aluminosilicate source mineral or industrial waste material with an alkali metal hydroxide or a mixture of an alkali metal silicate and hydroxide. The setting characteristics of the resulting mixture can be controlled by adjusting the molar composition of the component oxides; in the case of metakaolin precursors, a molar ratio of SiO2/Al2O3 = 3, M2O/SiO2 = 0.3 and H2O/M2O = 10 was reported [2] to set well and give a product with good strength, but these ratios can vary quite widely.…”
Section: Aluminosilicate Geopolymers: Composition Synthesis and Structurementioning
confidence: 99%
“…A further advantage of these materials over OPC is that they can be produced at temperatures from ambient to 80 • C by alkali activation of a range of aluminosilicate minerals [2][3][4][5][6], although geopolymers are now known to be less ecologically-friendly than previously claimed, given the production of the alkali activator and factors such as the energy-intensive processes by which some geopolymer precursors are produced [7]; these factors have often been overlooked or ignored by earlier proponents of geopolymers. Nevertheless, to date, the major interest in geopolymers has been as alternatives to OPC, although they have many other high-technology applications [8]. One such area of increasing interest is the mitigation of global environmental pollution problems, particularly air and water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Several synthetic methods for aluminosilicate geopolymers have been reported [8], but the most widely used is the reaction of a finely divided aluminosilicate source mineral or industrial waste material with an alkali metal hydroxide or a mixture of an alkali metal silicate and hydroxide. The setting characteristics of the resulting mixture can be controlled by adjusting the molar composition of the component oxides; in the case of metakaolin precursors, a molar composition of SiO2/Al2O3 ̴ 3, M2O/SiO2 ̴ 0.3 and H2O/M2O ̴ 10 is reported [2] to set well and give a product with good strength, but these ratios can vary quite widely.…”
Section: Aluminosilicate Geopolymers: Composition Synthesis and Strumentioning
confidence: 99%
“…A further advantage of these materials over OPC is that they can be produced at temperatures from ambient to 80 o C by alkali activation of a range of aluminosilicate minerals [2][3][4][5][6][7]. For this reason, to date the major interest in geopolymers has been as alternatives to OPC, although they have many other high-technology applications [8]. One such area of increasing interest is the mitigation of global environmental pollution problems, particularly air and water pollution.…”
Section: Introductionmentioning
confidence: 99%